Interaction between dietary L-carnitine and lipid levels on growth, lipid metabolism, and antioxidant capacity in juvenile golden pompano (Trachinotus ovatus) - Yuanming Yi; Haoyong Ma; Beiping Tan; Hongjie Wei; Jiahua Wu; Minling Mao; Jianwei Wu; Shuyan Chi; Hongyu Liu; Qihui Yang (Aquaculture Reports)
To evaluate the interaction between dietary L-carnitine (LC) and lipid levels on the lipid metabolism, antioxidant capacity and growth of juvenile golden pompano (Trachinotus ovatus), an 8-week trial was conducted. Six experimental diets were formulated by adding 0.02 % and 0.04 % LC to feeds with lipid levels of 9 %, 12 %, and 15 %, resulting in the following groups: C2L9, C4L9, C2L12, C4L12, C2L15, and C4L15. The results showed the weight gain rate and specific growth rate were significantly higher in the C4L15 group (P < 0.05), whereas the feed conversion ratio was significantly lower in the C2L12 group. Serum total cholesterol, alanine aminotransferase, and aspartate aminotransferase activities were higher in the L12 and L15 groups compared to the L9 group. The expression of cpt1 and atgl mRNA in the C4L12 group was significantly upregulated, whereas the expression of acc mRNA was significantly downregulated. The levels of lipid and LC significantly influenced malondialdehyde content and superoxide dismutase activity in the liver. At the same LC level, amylase and lipase activities tended to increase with higher lipid levels. Likewise, intestinal protease activity increased with increasing LC levels at the same lipid level. At the same LC level, foregut fold height significantly increased with higher lipid levels. Additionally, intestinal wall thickness was greatest in the C2L12 group. Higher lipid levels decreased gut flora diversity and abundance, promoting the growth of the pathogenic bacterium Photobacterium. Conversely, elevated LC levels positively impacted the abundance of the beneficial bacterium Mycoplasma and effectively reduced the abundance of the pathogenic bacterium Vibrio. Therefore, adding carnitine to high-lipid diets can help reduce lipid peroxidation in the liver of T. ovatus, improve lipid and carbohydrate utilization, promote intestinal development, and enhance the growth of beneficial gut bacteria.